RESEARCH OF SELF-ESTEEM OF YOUTH USING IMPLICIT ASSOCIATION TESTS AND SELF-REPORTED PROCEDURES - Plotka, Irina; Blumenau, Nina; Ozola, Elena; Pogildjakova, Svetlana; Drozdova, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Research aim is to investigate self-esteem of young people, using Single-Category Implicit Association Tests (SC-IAT) and self-reported procedures. Research questions: Are there differences between effects of implicit self-associations: performance, social, appearance and general? What factors can describe a set of measured implicit and explicit variables, characterizing self-esteem? Are the results of implicit and explicit measurements independent from each other? What are the features of the contribution of explicit global self-esteem, state self-esteem (performance, social, appearance) and implicit self-associations (performance, social, appearance) into the implicit general self-associations? Is there the compliance of measurement results of self-esteem obtained with SC-IAT and self-reported procedures? Method: Participants – 132, age 18-30 years (M=25.4, SD=4.0). Implicit measures: Modified versions of SC-IAT: SC-IAT_1 (Performance self-associations, D(P)), SC-IAT_2 (Social self-associations, D(S)), SC-IAT_3 (Appearance self-associations, D(A)), SC-IAT_4 (General self-associations, D(SA)), developed on the basis of SC-IAT. Explicit measures: Rosenberg Self-Esteem Scale and State Self-Esteem Scale by Heatherton and Polivy. Results: Partial correspondence of measurements’ results using IAT and self-reported procedures was found. It was found that the main contribution to the General self-associations is made by the Social self-associations, Appearance self-associations and Rosenberg’s Self-Esteem. The results of implicit and explicit measurements are independent from each other.